2007
DOI: 10.1113/jphysiol.2007.142737
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes play a critical role in transient heterosynaptic depression in the rat hippocampal CA1 region

Abstract: Active synapses can reduce the probability of transmitter release at neighbouring synapses. Depending on whether such heterosynaptic depression is mediated by intersynaptic diffusion of transmitter or by release of gliotransmitters, astrocytes should either hinder or promote the heterosynaptic depression. In the present study we have examined the developmental profile and astrocytic involvement in a transient heterosynaptic depression (tHeSD) in the CA1 region of the rat hippocampal slice preparation. A short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 50 publications
5
93
1
Order By: Relevance
“…By responding to presynaptically released glutamate and by releasing gliotransmitters, the astrocyte part of the tripartite synapse is strategically positioned to modulate release probability in an activity-dependent manner (Newman, 2003). Indeed, several studies have shown that gliotransmitters can modulate release probability at cortical synapses (Robitaille, 1998;Serrano et al, 2006;Zhang et al, 2003;Liu et al, 2004;Pascual et al, 2005;Andersson et al, 2007;Jourdain et al, 2007), and we now show that astrocytes play an active role in mediating homosynaptic short-term synaptic depression.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…By responding to presynaptically released glutamate and by releasing gliotransmitters, the astrocyte part of the tripartite synapse is strategically positioned to modulate release probability in an activity-dependent manner (Newman, 2003). Indeed, several studies have shown that gliotransmitters can modulate release probability at cortical synapses (Robitaille, 1998;Serrano et al, 2006;Zhang et al, 2003;Liu et al, 2004;Pascual et al, 2005;Andersson et al, 2007;Jourdain et al, 2007), and we now show that astrocytes play an active role in mediating homosynaptic short-term synaptic depression.…”
Section: Introductionmentioning
confidence: 51%
“…2 A), emerging at postnatal day 10 and being fully developed at postnatal day 20, would thus be more consistent with activity-induced release of gliotransmitters from astrocytes than with spillover. To more directly test whether the PBD required some form of astrocyte signaling, we elicited the PBD before and after the application of the glial metabolic inhibitor FAc (Fonnum et al, 1997;Andersson et al, 2007). Consistent with a critical role for astrocyte signaling, FAc completely blocked the PBD (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Astrocytes have been reported recently to have a functional role in neuronal excitability (Araque et al, 1998a;Haydon and Carmignoto, 2006), heterosynaptic depression (Pascual et al, 2005;Serrano et al, 2006;Andersson et al, 2007), cerebrovascular dynamics (Zonta et al, 2003;Straub and Nelson, 2007), and pathological states such as epilepsy Tian et al, 2005;Fellin et al, 2006a). One unifying feature of these findings is that astrocyte modulation of these processes occurs via a Ca 2ϩ -dependent release of "gliotransmitters," including ATP (which is converted to adenosine by ectonucleotidases) and glutamate (Montana et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Later studies demonstrated that this process can be observed in acute brain slices[71,72,73,74,75,76,77,78,79] and in vivo [80]. Astrocytes were later shown to release a number of chemical transmitters, including ATP[81,82,83,84,85], D-serine[86,87,88,89], TNF-alpha[90,91], and ANP[92], in a process that has recently been termed gliotransmission[93]. Based on the early studies of gliotransmission, the concept of the tripartite synapse was proposed[94], highlighting the role of the astrocyte as a third active element in information processing at the synapse[95,96,97,98,99].…”
Section: Astrocytes As Neuromodulatorsmentioning
confidence: 99%